2004
DOI: 10.1111/j.1550-7408.2004.tb00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Composition of Pneumocystis jirovecii with Blocked 14α‐Demethylase Activity

Abstract: Several drugs that interact with membrane sterols or inhibit their syntheses are effective in clearing a number of fungal infections. The AIDS-associated lung infection caused by Pneumocystis jirovecii is not cleared by many of these therapies. Pneumocystis normally synthesizes distinct C28 and C29 24-alkylsterols, but ergosterol, the major fungal sterol, is not among them. Two distinct sterol compositional phenotypes were previously observed in P. jirovecii. One was characterized by delta7 C28 and C29 24-alky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Sterols were extracted from S. cerevisiae cells, purified by biphasic partitioning, and neutral lipid fraction was obtained using silicic acid column chromatography as previously described (Giner et al. , ; Kaneshiro et al. ; Nkinin et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sterols were extracted from S. cerevisiae cells, purified by biphasic partitioning, and neutral lipid fraction was obtained using silicic acid column chromatography as previously described (Giner et al. , ; Kaneshiro et al. ; Nkinin et al.…”
Section: Methodsmentioning
confidence: 99%
“…Individual sterols were isolated from total sterol samples (> 500 μg) by a combination of thin‐layer chromatography and high performance liquid chromatography (HPLC) (Giner et al. , 2006; Nkinin et al. ) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, definitive structural identities of 28 sterols were elucidated for P. jirovecii with blocked 14DM activity. Individual sterols were isolated by TLC and HPLC and analyzed by NMR (75). These analyses confirmed that the major noncholesterol components had a methyl group at C-14 of the sterol nucleus ( Table 6).…”
Section: Human-derived P Jirovecii: Possible Erg11 Mu-tant Population?mentioning
confidence: 72%
“…The sterol composition of human-derived P. jirovecii has been reported (Kaneshiro et al, 1999a;Giner et al, 2004). There appears to be two distinct P. jirovecii populations (strains) that differ in their sterol profiles.…”
Section: Recombinant Pneumocystis Sterol Biosynthesis Enzymesmentioning
confidence: 99%
“…in P. jirovecii populations with high C 31 and C 32 sterols, the lanosterol derivative pneumocysterol (Kaneshiro et al, 1999b) (24Z)-ethylidenelanost-8-en-3b-ol can accumulate often comprising about half the Pneumocystisspecific sterols. Definitive structural analyses of sterols in a population with high C 31 and C 32 sterols indicated that those P. jirovecii organisms lacked 14DM activity (14DM -) (Giner et al, 2004). 24-alkyllanosterol derivatives comprised almost 90 % of P. jirovecii 14DM -whereas P. carinii isolated from rat lungs has only 5 % of these sterols.…”
Section: Recombinant Pneumocystis Sterol Biosynthesis Enzymesmentioning
confidence: 99%